(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
“Get Finland Moving” programme (2024–2027) is part of the government’s goal to increase physical activity across all age groups in Finland. One of the programme’s initiatives is the promotion of physical activity and nutrition among professionals. This Liira initiative covers the entire country and aims to develop effective and high-quality physical activity counselling and nutritional health services, based on the idea that regular exercise and a healthy diet significantly improve wellbeing. The initiative seeks to support strategic choices, strengthen collaborative structures, implement impactful operational models, and enhance professionals’ expertise through nationwide training. This includes, among other things, referring individuals who engage in insufficient physical activity from healthcare services to physical activity counselling through official referrals. Competence Mapping and Training Development: In 2024, the Ministry of Social Affairs and Health conducted a comprehensive training needs survey targeting regional healthcare services and municipal physical activity services – an unprecedented survey for this target group. Key development areas identified include: · Functional and high-quality service chains · Seamless collaboration between physical activity and nutrition (e.g. dietitian referrals to exercise counselling) · Motivation and behaviour change · Promotion of healthy lifestyles · Effectiveness of exercise counselling A nationwide training tour in 2025 will enhance professionals’ expertise, increase the visibility of physical activity and nutrition in healthcare, and strengthen cooperation. Within two years, the vision is to integrate standardised and high-quality supplementary training in physical activity and nutrition into all healthcare education programmes in Finland, supporting professional collaboration. Implementation and Evaluation: New operating models will be actively implemented and disseminated nationwide through strong ministerial communication and networking. The effectiveness of the measure will be evaluated as part of the “Get Finland Moving” programme throughout the government term.